Combined double superficial circumflex iliac artery perforator flap with lymphatic tissue preservation and lymphovenous anastomosis for lymphatic sequelae prevention in thigh defect reconstruction: A case report. Issue 3 (13th February 2021) - Scaglioni, Mario F.; Meroni, Matteo; Fritsche, Elmar; Fuchs, Bruno
Abstract: The thigh region is often site of soft tissue tumors development. Leiomyosarcoma, in particular, is a malignant tumor that, if not promptly treated, presents a growth rate that often results in large masses. The safest treatment in these cases is margin‐free extensive surgical resection. This leads to rather large defects that in a delicate region, such as the medial thigh, implies a series of possible complications from the lymphatic point of view. In this region run major lymphatic vessels, appointed to drain the whole leg. Now that one is aware of this issue, the best solution is trying to obtain an efficient reconstruction and preventing the development of postoperative lymphedema and lymphocele. Here, we present a case of great saphenous vein leiomyosarcoma resection in the right medial thigh reconstructed by means of two superficial circumflex iliac artery perforator (SCIP) flaps with lymphatic tissue preservation, combined with preventive lymphovenous anastomosis (LVA). A 67‐years‐old woman presented a 22 × 16 cm soft tissue defect after the surgical excision. To fill the defect, we resorted to a larger SCIP flap island, supplied by both the superficial and deep branches of the superficial circumflex iliac artery anastomosed in perforator‐to‐perforator fashion, and to a smaller SCIP flap island supplied only by the superficial branch. Before surgery, the lymphatic vessels running in the flaps area were identified with indocyanine green lymphography and were carefully preserved during the harvest procedure. They were then transferred with the surrounding tissue and orientated in order to match the lymphatic flow direction, providing further fluid drainage. To boost the lymphatic drainage, an LVA was also performed at the superior‐edge‐of‐the‐knee incision point joining a functioning lymphatic vessel to a nearby reflux‐free vein. The postoperative course was uneventful and at 7 months follow‐up, the patient showed good cosmetic and functional outcomes with no swelling and no signs of tumor relapse. This report provides a series of technical insights and adds further evidence to support the efficacy of this procedure for management of soft tissue defects in the medial thigh region.